2001
DOI: 10.1161/hs0901.094287
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Protects Against Long-Lasting Behavioral and Morphological Consequences of Neonatal Hypoxic/Ischemic Brain Injury

Abstract: Background and Purpose-Recent studies suggest that statins (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) not only reduce the incidence of stroke by lowering cholesterol levels but may also exert neuroprotective effects via a mechanism not related to their lipid-lowering effect. Despite the growing body of evidence, however, the neuroprotective effect of statins in stroke is still controversial. Herein, we studied whether a prophylactic administration of simvastatin (Sim) provides significant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 31 publications
7
43
0
Order By: Relevance
“…15 It should be noted that most neuroprotective treatments, including hypoxic preconditioning, 16 reduce inflammation, perhaps also as a consequence of the minor number of cells that undergo necrosis. Our study also showed that hypoxic preconditioning and simvastatin, which have neuroprotective effects in neonatal HI, [16][17][18] increased beclin 1 expression. 8 Increased beclin 1 expression, which correlated with the onset of protection, has been previously reported in an in vivo model of myocardial stunning, 19 and a recent paper that studied the role of autophagy in palmitate-induced beta cell death concluded, according to our hypothesis, that autophagy delays beta cell loss in type 2 diabetes.…”
supporting
confidence: 74%
“…15 It should be noted that most neuroprotective treatments, including hypoxic preconditioning, 16 reduce inflammation, perhaps also as a consequence of the minor number of cells that undergo necrosis. Our study also showed that hypoxic preconditioning and simvastatin, which have neuroprotective effects in neonatal HI, [16][17][18] increased beclin 1 expression. 8 Increased beclin 1 expression, which correlated with the onset of protection, has been previously reported in an in vivo model of myocardial stunning, 19 and a recent paper that studied the role of autophagy in palmitate-induced beta cell death concluded, according to our hypothesis, that autophagy delays beta cell loss in type 2 diabetes.…”
supporting
confidence: 74%
“…HP and CoCl 2 preconditioning were able to reduce the extent of cortical injury and only HP reduced striatal damage. Although many treatments have been tested in the HI model at short term intervals, only a few have been examined and found to yield long-term functional outcomes (3,16,26,27). Using preconditioning with hypoxia and two hypoxia-mimetic compounds, CoCl 2 and DFX, we observed long-term protective actions of these treatment strategies.…”
Section: Discussionmentioning
confidence: 91%
“…Those genes affected include HIF-1 (9) and HIF-1 target genes: glucose transporters, glycolytic enzymes (10), erythropoietin and vascular endothelial growth factor (VEGF) (11). Numerous experimental studies have highlighted the need to examine long-term functional improvements in addition to histologic outcomes after HI injury in the neonate (3,15,16). Therefore, we have investigated whether preconditioning with hypoxia (HP), DFX and CoCl 2 has long lasting cytoprotective actions and thus improves both morphologic and behavioral endpoints 5 wk after an HI insult performed in postnatal day 7 rat pups.…”
mentioning
confidence: 99%
“…26 Because we did not perform qualitative histology to characterize the various cellular subtypes of the brain parenchyma, subtle injury to neuronal cells involved in behavioral learning cannot be excluded. 27 Future studies should include both morphological study and neurochemical studies, such as neurotrophic factors and neurotransmitters.…”
Section: Five-day Treatment Improved Histology But Not Behaviormentioning
confidence: 99%